Exploring the protective effects of coenzyme Q10 on female fertility - Jiang, Yu; Han, Yao; Qiao, Pengyun; Ren, Fa (Frontiers in Cell and Developmental Biology, 2025)
The global decline in fertility rates has intensified the reliance on assisted reproductive technology (ART) for infertility treatment. Antioxidant supplementation, particularly with coenzyme Q10 (CoQ10), has gained prominence as a therapeutic strategy to enhance fertility outcomes and ART success. As a lipid-soluble benzoquinone, CoQ10 plays dual roles in the metabolism of mitochondrial energy and antioxidant protection. By regulating oxidative stress and reducing reactive oxygen species (ROS), CoQ10 improves oocyte quality, ovarian function, and mitochondrial efficiency, thereby optimizing ART outcomes. Clinical studies demonstrate that CoQ10 supplementation enhances ovarian function, increases the number of eggs, and improves the quality of embryo, particularly in women with weak ovarian reserve functions or older age. This review synthesizes current evidence on CoQ10’s mechanisms in safeguarding female fertility, including its effects on oocyte maturation, embryonic development, and ovarian aging. Furthermore, it explores CoQ10’s potential in addressing conditions such as premature ovarian failure and polycystic ovary syndrome. This review provides an overview of CoQ10’s protective effect on female fertility and its potential clinical application in reproductive medicine, aiming to offer guidance for the future use of CoQ10 in ART clinical practice.